PSYCHOLOGICAL ADAPTATION AS A CONDITION OF FORMATION INNOVATIVE PERSONALITY OF STUDENTS SECONDARY SCHOOL (Pedagogy of Higher and Secondary Education, 2007)
In the article the author define program to the formation of the innovation personality pupil, open problem anxiety. There are revealed which stopped its development. This article considers the establishment and mould experiments.